PECULIARITIES OF IDENTITY FORMATION IN NEW SOCIOCULTURAL REALITIES - Chenbai, Natalia (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2025)
. In contemporary society, transformations are taking place that influence the formation of a new type of personality, one who chooses their own model of existence in a contradictory world. Objectively, only those human characteristics that can contribute to both the progressive development of the individual and society as a whole are in demand. These dynamics have led to the necessity of exploring the problem of identity, whose formation occurs within the framework of cyberculture’s achievements. The aim and tasks involve identifying the peculiarities of identity formation in the context of the dominance of cyberculture values, which generate numerous new opportunities for individuals. Research methods. An important methodological tool of the research is the sociocultural approach, along with the principles of historicism and systemic analysis. The theoretical and methodological foundation of this study rests on the works of philosophers who have explored the phenomenon of identity across various historical and cultural epochs. Research results. In contemporary society, there is a renewed surge of interest among researchers in the issues of self-identity and social identity. Significant contributions to the study of these problems have been made by existentialist concepts, while postmodern philosophy has proclaimed the notion of "zero identity," emphasizing that today it is only possible to speak of a multiplicity of identities and even the absence of a need for self-identity. Individuals are encouraged to free themselves from the constraints associated with the concept of identity and to embrace their uniqueness and fluidity as an integral part of life. Discussion. The modern personality is shaped by cyberculture, resulting in the emergence of a new type of personality—virtual or networked—characterized by internal multiplicity. This new environment leads to the devaluation and desacralization of the individual; their development is determined by the process of interpretation, and their formation aligns with the demands of the networked society and networked culture. Consequently, identity becomes a mechanism that aids adaptation to the reality in which individuals live. Conclusions. As society evolves, notions of identity naturally undergo transformations, driven by changes in the cultural environment and people’s lifestyles. The fundamental condition for personality formation in today’s dynamic world is the ability to choose one’s own identity, with the right to modify and shape its components in accordance with core value orientations